Recent Developments in Formulation Design of a Multifunctional Phytochemical Quercetin: A Review - Mallya, Rashmi; Patil, Kunal (Pharmacognosy Reviews)
Quercetin is a polyphenolic flavonoid, found naturally and widely distributed in many plants. Quercetin has a plethora of activities and due to its diverse activity profile and multifunctionality on various targets, it has become an upcoming area of interest for several researchers. Evidences suggest that researchers have put up a way forward and explored the novel approach of quercetin lipid-based formulations. Recent literature studies indicate that lipid-particulate, emulsion and vesicular systems were found to be successful in comparison to the conventional formulations. These formulations comprise of a suitable combination of natural lipids with surfactants, cosurfactants and cosolvents. Customizing lipid nanoparticles with quercetin to a particular target may also be a revolutionary method in order to optimize the therapeutic activity of drugs and mitigate toxicity. There is an increasing need to develop these novel formulations as they enhance the solubility profile, improves stability and has an expanded biological profile. Regardless of its enormous potential linked with the delivery of several lipophilic drugs with improved bioavailability using novel lipid-based nano-formulations, these lipid formulations have certain drawbacks, which limits its commercialization and market potential. This review updates and increases knowledge about quercetin-lipid based formulations having anticancer, anti-inflammatory, antioxidant, dermatological and CNS activity as well as those useful in treating several bone disorders. This review also compiles recent advances in methods, formulation composition, targets, experimental models and route of administration for quercetin containing lipid-based formulations.
Keywords: Anticancer; Antioxidant; Lipid-based drug delivery; Quercetin; Vesicular systems.